2019
DOI: 10.1097/md.0000000000014834
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of blood inflammatory biomarkers NLR, PLR, and LMR in cancer—A protocol for systematic review and meta-analysis

Abstract: Background: The neutrophil-lymphocyte-ratio, platelet-lymphocyte-ratio, and monocyte-lymphocyte-ratio have been explored as a simple, inexpensive, and effective method for cancer prognosis. However, there are no studies that have investigated the comparative utility of these markers, in multiple cancers. Methods: The preferred reporting items for systematic review and meta-analysis protocols (PRISMA-P) guidelines were used to design this meta-analysis protocol. The fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 46 publications
(41 reference statements)
1
89
0
4
Order By: Relevance
“…The HPR was calculated as haemoglobin divided by the platelet count (Tang et al , ). The PLR was determined as the platelet count divided by the lymphocyte count (Kumarasamy et al , ). This study was carried out in accordance with the Helsinki Declaration and its amendments and endorsed by the institutional review board of each participating institution.…”
Section: Methodsmentioning
confidence: 99%
“…The HPR was calculated as haemoglobin divided by the platelet count (Tang et al , ). The PLR was determined as the platelet count divided by the lymphocyte count (Kumarasamy et al , ). This study was carried out in accordance with the Helsinki Declaration and its amendments and endorsed by the institutional review board of each participating institution.…”
Section: Methodsmentioning
confidence: 99%
“…Inflammation is closely related to tumour progression and prognosis. Over the past few decades, immune cell-related indices such as the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-tomonocyte ratio (LMR) have been used to predict prognosis and recurrence in various malignancies [2]. In recent years, a novel inflammatory marker, the systemic inflammation response index (SIRI), which is calculated using the levels of neutrophils, monocytes, and lymphocytes, has shown an ability to predict prognosis in pancreatic cancer [3], gastric cancer [4], and nasopharyngeal cancer [5].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of circulating leukocyte subsets has become the most convenient method, especially for the analysis of NLR, PLR and MLR. Numerous studies have con rmed that they link to the prognosis of different cancers such as gastric cancer, ovarian cancer and colorectal cancer (15,16,(23)(24)(25). NLR, PLR and MLR are known to be predictors of pathological response in LARC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have paid more attention on systemic in ammatory response indicators for predicting the prognosis of rectal cancer after CRT (11)(12)(13). In particular, neutrophil-lymphocyte-ratio (NLR), monocytelymphocyte-ratio (MLR) and platelet-lymphocyte-ratio (PLR) are considered as prognostic biomarkers for patients with rectal cancer (13)(14)(15)(16). Some studies have suggested that pre-CRT NLR and PLR, or NLR alone are independently related to tumor response (17,18).…”
mentioning
confidence: 99%